Assessing Prospective Biology Teachers (PBTs) Perceptions on Thinking as a 21st Century Skill: A Case Study at Islamic University (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The explanatory mixed-method was conducted to assess prospective biology teachers’ (PBTs) perceptions on thinking as 21st century skills. Data were collected using a quantitative survey method, and an interview with PBTs from Islamic University. 168 (14 men and 154 women) of 195 PBTs participated in filling out the questionnaire. The questionnaire consisted of 24 statements of aspects of critical thinking, problem-solving, creativity, metacognition of the 21st century skill. The confirmatory factor analysis (CFA) and alpha Cronbach tests were used to determine the quality of the instrument. Statistic descriptive, ANOVA, and correlation tests were conducted to analyze the quantitative data. Triangulation was conducted on the results of the interview. The results of the study indicate that (a) most male and female PBTs at Islamic universities have high skills in critical thinking and metacognition; (b) most male and female PBTs at Islamic universities have insufficient skills in problemsolving and creativity skills; (c) the results of this study also showed that there is no relationship between gender and PBTs skills. This study suggested that teachers and education managers in Islamic universities need to apply integrative learning by paying attention to the skills needed by PBTs. Learning applied in classrooms should be based on 21st century skills.